Effects of acute and chronic ammonia exposure on survival, growth and intestinal microbiota composition of hybrid carp - Yu Han; Xiaoqian Li; Xue Li; Shidong Wang; Muzi Zhang; Ming Li (Aquaculture Reports)
It is very important to evaluate the growth tolerance threshold of fish under long-term low ammonia exposure for water quality management in aquaculture. This study employed a sequential method to evaluate the tolerance of hybrid carp to both acute and chronic ammonia exposure. In stage 1, we estimated the effects of acute high ammonia stress on hybrid carp and based on linear interpolation (y = 0.0047x - 0.4659, where R2 = 0.9448, with y representing cumulative mortality and x representing ammonia concentration), the 96-h LC50 was determined to be 206.38 mg/L of total ammonia (TA). In stage 2, the long-term low ammonia exposure ranges (< 0.001 (control), 1.03 (LC50/200), 2.05 (LC50/100), 4.11 (LC50/50), and 8.21 (LC50/25) mg/L TA) were determined based on 96-h LC50 value, and then a 6-week experiment was performed. The results showed that elevated ammonia concentration (> 1.03 mg/L TA) significantly reduced food intake. The growth performance was inhibited at ammonia concentrations above 1.03 mg/L TA, while survival rate decreased at ammonia concentrations above 4.11 mg/L TA. The lack of free amino acids (arginine, leucine, aspartic acid, and glutamine) not only affect the fish growth, but also inhibits the key enzymes (arginase and argininosuccinic acid lyase) activity in urea cycle, resulting in a decrease in ammonia detoxification ability. Even exposure to low concentration of ammonia (2.05 mg/L TA) can reduce the activity of antioxidant enzymes (superoxide dismutase and catalase), causing liver damage and inflammation. Long-term low ammonia exposure reduces intestinal microbiota richness and diversity while increasing relative abundance of harmful bacteria, such as Leifsonia, Aeromonas, Erysipelothrix, and Acinetobacter. And the increase in relative abundance of beneficial bacteria such as Cetobacterium may be a coping strategy against ammonia toxicity. We recommend against exposing hybrid carp to ammonia concentrations exceeding 1.03 mg/L TA for prolonged periods of time.